The Regulatory-associated protein of target of rapamycin 1B (RAPTOR 1B) interconnects with the photoperiod pathway to promote flowering in Arabidopsis - Reynel Urrea-Castellanos; Maria J. Calderan-Rodrigues; Anthony Artins; Magdalena Musialak-Lange; Appanna Macharanda-Ganesh; Alisdair R. Fernie; Vanessa Wahl; Camila Caldana (Proceedings of the National Academy of Sciences, 2025)
The transition from vegetative to reproductive growth, or floral transition, is a tightly regulated, energy-demanding process. In Arabidopsis , the interplay of light perception and circadian rhythms detects changes in photoperiod length, accelerating flowering under long days (LD). CONSTANS (CO), a transcription factor, upregulates FLOWERING LOCUS T (FT) in leaves during dusk. The FT protein then moves to the shoot apical meristem, triggering the floral transition. While light and circadian signals control CO protein levels, less is known about how the nutrients/energy sensing regulates the photoperiod pathway for flowering modulation in this process. In our study, we identify the contribution of the Regulatory-associated protein of target of rapamycin 1B (RAPTOR1B), a component of the nutrient-sensing TOR complex (TORC), in the induction of specific flowering genes under CO control. While transcription of CO remains unaffected in raptor1b mutants, a reduction in its protein levels at dusk is observed compared to the wild type. Remarkably, the mutant also exhibits compromised GIGANTEA (GI) protein levels, crucial for CO stabilization during dusk. Our results indicate that the interaction and colocalization of RAPTOR1B with GI in the nucleus might influence GI levels through an unknown posttranscriptional mechanism. Genetic crosses position RAPTOR1B upstream of CO and GI. This is supported by phenotypic and molecular analyses. Our findings demonstrate that RAPTOR1B, likely as part of TORC, contributes to the photoperiod pathway of the flowering network, ensuring the timely initiation of floral transition under LD conditions.